Sn-Sb-Se crystalline phases formed by melt-quenching technique - Adam, A. B.; Sakrani, Samsudi; Wahab, Y. (Springer Netherlands, 2006)
Preperation of alloy percentages of Sn-Sb-Se(TAS) of shaking furnace and melt sealing evacuated quartz ampoule using melt quenching technique (MQT) was analyzed. XRD measurement was carried out to identify whether the prepared samples were amorphous or crystalline structure and to determine the boundary between the two states. SEM morphological studies revealed that increasing Sn and Sb mole % modify the microstructure of the ternary Sn-Sb-Se based systems. Under the same conditions of preparation and maintaining Sn mol% at 15, the dendrite shapes of crystals were enlarged when Sb mol% increased. The Sn occurred in ternary compositions and supports the theoretical argument which considered Sb-mol %=14.3 is the boundary line between the crystalline and crystalline phase is dominant in the region with Sb-mol% more than or equal to 15. MQT proved its ability in preparing alloy of Sn-Sb-Se in crystalline structure and there was no excessive loss of the materials during the preparation.